The Existence of Sumang Culture in Strengthening Students' Character - Suprapto, Edy; Rahmi Novalita, Rahmi Novalita; Fitrah, Hariki (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
This research aims to describe the existence of sumang culture in strengthening student character. The research was conducted at State Elementary School 03 Jagong Jeget, Central Aceh Regency. The reason for choosing the research location was because the school implemented sumang culture as a school culture in strengthening student character. The informants in this research were key informants, namely the school principal, teachers and students. The technique for taking informants uses the snowball sampling technique. Data collection techniques use observation, interviews and documentation. Data analysis techniques use data reduction, data display, and drawing conclusions. The results of the research show that Sumang culture contains character values, namely religious, responsible, peace-loving, honest, creative, democratic, hard work, discipline. The supporting factors for implementing Sumang culture are; environmental factors, facilities and infrastructure, curriculum, and support from students' parents.